Follow-up after acute Pulmonary Embolism - Klok, Frederikus A.; Barco, Stefano (Hämostaseologie, 2018)
In addition to among others major bleeding from anticoagulant therapy and recurrent venous thromboembolism (VTE), patients who survived acute pulmonary embolism (PE) face an increased risk of chronic functional limitations and decreased quality of life. In recent years, this latter complications have been better framed within the evolving definition of “post-PE syndrome” of which chronic thromboembolic pulmonary hypertension (CTEPH) represents the most extreme presentation. The post-PE syndrome in all its aspects is a frequent and clinically relevant long-term complication of PE but -except for CTEPH- has been largely understudied. There is great need to better define and understand the natural course of acute PE, to predict the development of the post-PE syndrome and to evaluate the potential benefits evolving treatments such as cardiopulmonary rehabilitation.
Keywords: Pulmonary embolism; CTEPH; post-PE syndrome; quality of life